2022
DOI: 10.5194/acp-22-6365-2022
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of new particle formation events in Helsinki during a Baltic Sea cyanobacterial summer bloom

Abstract: Abstract. Several studies have investigated new particle formation (NPF) events from various sites ranging from pristine locations, including forest sites, to urban areas. However, there is still a dearth of studies investigating NPF processes and subsequent aerosol growth in coastal yet semi-urban sites, where the tropospheric layer is a concoction of biogenic and anthropogenic gases and particles. The investigation of factors leading to NPF becomes extremely complex due to the highly dynamic meteorological c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 148 publications
(169 reference statements)
1
6
0
Order By: Relevance
“…However, atmospheric bases such as DEA, TMA, and dimethylamine (DMA) present almost a negligible role. Based on previous studies, MSA and SA also have a high EP on the nucleation with HIO 3 as the partner. ,, It should also be noted that while iodine and sulfur oxoacids are ubiquitous in the polar and marine atmospheres, ,,, the evidence of widespread amines in marine and polar atmospheres remains sparse and weak. Therefore, MSA and SA could potentially have the highest EP for HIO 3 –HIO 2 -driven nucleation by considering their EP on both nucleation with HIO 3 as the partner and nucleation with HIO 2 as the partner, although we remain open to future field evidence of amines in the marine and polar atmospheres.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, atmospheric bases such as DEA, TMA, and dimethylamine (DMA) present almost a negligible role. Based on previous studies, MSA and SA also have a high EP on the nucleation with HIO 3 as the partner. ,, It should also be noted that while iodine and sulfur oxoacids are ubiquitous in the polar and marine atmospheres, ,,, the evidence of widespread amines in marine and polar atmospheres remains sparse and weak. Therefore, MSA and SA could potentially have the highest EP for HIO 3 –HIO 2 -driven nucleation by considering their EP on both nucleation with HIO 3 as the partner and nucleation with HIO 2 as the partner, although we remain open to future field evidence of amines in the marine and polar atmospheres.…”
Section: Resultsmentioning
confidence: 97%
“…a factor of 3 in J for the HIO 3 −HIO 2 system ([HIO 3 ] = 10 7 cm −3 ). It is worth mentioning that such ambient conditions are reachable in realistic marine atmospheric boundary layer, e.g., Helsinki 48 and Ny-Ålesund. 41 In addition, in some specific regions where [MSA] is higher and [HIO 3 ] is relatively lower, the enhancing potential of MSA will become more prominent for iodine oxoacid nucleation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They can also be directly emitted by vegetation and from cooking. , They are observed both in the gas and particle phases and are known to stabilize the prenucleation clusters by binding strongly with other species in the atmosphere. The concentration of acetic acid was measured to be in the range of 1.5–8.4 × 10 10 molecules cm –3 in northwestern USA and 0.5–43.8 × 10 10 molecules cm –3 at an urban site in California. , Among dicarboxylic acids, oxalic acid is the most prevalent, with concentrations ranging from 10 7 to 10 9 molecules cm –3 in urban and nonurban atmospheres. In certain remote locations, carboxylic acids can account for as much as 80–90% of acidity in the precipitation. , They can also contribute to the formation of cloud condensation nuclei. , SA and iodic acid (IA) are well-known drivers of tropospheric nucleation processes. ,, Daytime SA concentrations are estimated to be in the range of 10 6 –10 7 molecules cm –3 or below in most urban and remote locations and it can even reach up to 10 8 molecules cm –3 in polluted environments. The concentration of IA in the polluted urban environment of Beijing and Nanjing reaches up to 10 6 molecules cm –3 in the summer months . The IA concentration sourced by biogenic emissions near coastal environments can even reach up to 10 8 cm –3 . ,, …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cyanotoxins, cyanobacterial DNA, and other molecular tracers of CHABs have been detected in airsheds during CHABs. Cyanobacteria and their metabolites are theorized to be aerosolized via bubble-bursting, wave action, and related processes, leading to the emission of primary aerosols carrying CHAB-derived cells and compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Several CHAB forming genera, including Aphanizomenon , Dolichospermum , and Microcystis are associated with increased VOC detection in water. CHABs are correlated with PM 2.5 in the airshed of several diverse aquatic systems, including the Baltic Sea, a eutrophic estuary in eastern North Carolina, USA, and a small lake in central Ohio, USA . Recent work has also suggested that the microbial “volatilome”, comprised of all the characterized and uncharacterized volatile compounds produced by a bacterial species/community, is an untapped reservoir, holding key information regarding microbial biochemical and ecological function.…”
Section: Introductionmentioning
confidence: 99%